Understanding the Gaps of Guidance and Counseling through the Lens of School Guidance Advocates - Gragasin, Reann Vee C. (International Journal of Research in Interdisciplinary Studies, 2024)
This phenomenological study explored the experiences of guidance advocates in the execution of their guidance and counseling duties in the public secondary schools of Banaybanay District, Division of Davao Oriental. Furthermore, this investigated their coping strategies and insights that were derived from their experiences drawn from the findings of this study. Qualitative – phenomenological study was employed in exploring the views of the ten participants of which primary instrument of data gathering was through in- depth interview. After analyzing the responses of the participants about their experiences as guidance advocates in guidance and counseling, the following three themes emerged: experiencing difficulty in adjusting as designate guidance advocate, adapting to responsibility, and struggling to complete tasks. Further, on the participants’ coping mechanisms of guidance advocates in guidance and counseling, the following three themes emerged: focusing on helping the learners, adapting various strategies to improve guidance services, and collaborating with other guidance advocates. Finally, after analyzing the responses of the participants about the insights of guidance advocates drawn from the findings of the study, the following three themes emerged: giving importance to teachers’ trainings and seminars, implementing programs and activities for students, and providing needed facilities. It implies that students are provided with guidance and counseling services in order to help them find answers to psychological issues that may be interfering with their academic performance. The pupils are able to build abilities in problem-solving through the application of this method, which in some ways assists them in dealing with certain challenges surrounding their life. It was absolutely necessary to direct students to exhibit acceptable attitude and behavior within and outside the school.